Nursing Care Analysis on Mrs. R with Rheumatoid Arthritis and Ginger Water Compress Interventions - Gunadi, M. Luthfiansyah; Ridwan Rifai, Mohammad (CV. Literasi Publikasi Indonesia, 2024)
This case study examines the nursing care of Mrs. R, who was diagnosed with Rheumatoid Arthritis (RA), focusing on the application of ginger water compresses to reduce chronic pain. The study was conducted in Desa Tegal Panjang, Kecamatan Sucinaraja, Garut, Indonesia. The primary nursing diagnosis was chronic pain related to joint inflammation. The nursing interventions, based on Evidence-Based Practice, included the application of warm ginger water compresses. The results indicated a significant reduction in pain intensity, supporting the effectiveness of ginger compress therapy in managing pain associated with RA.